Flexibility windows in faujasite with explicit water and methanol extra-framework content. Issue 13 (3rd December 2014) - Wells, Stephen A.; Leung, Ka Ming; Edwards, Peter P.; Sartbaeva, Asel
Abstract : Geometric simulations reveal limits on flexibility in a zeolite framework (faujasite) with extra-framework methanol and water contents explicitly present. Abstract : We present geometric simulations on a zeolite framework (faujasite) with extra-framework methanol and water contents explicitly present. We distinguish the intrinsic flexibility window of the framework from the newly defined extrinsic window limited by host–guest steric interactions. The extrinsic flexibility window can be limited not only in compression, but also in expansion, as the beta-cages in a maximally expanded framework lack the flexibility to adapt bulky contents such as a combination of methanol and water molecules. Our simulations suggest a reinterpretation of extra-framework content nominally refined as water sites in compression experiments.